Trisomy 8 is Associated with Favorable Outcome in the Patients with Myelodysplastic Syndromes Treated with Allogeneic Hematopoietic Stem Cell Transplantation - Mamaev, Nikolay N.; Latypova, Maria V.; Gindina, Tatiana L.; Kanunnikov, Mikhail M.; Osipova, Anna A.; Bondarenko, Sergey N.; Riumin, Sergey S.; Zubarovskaya, Liudmila S. (Journal of Hematology Research, 2022)
Favorable prognostic significance of sole trisomy 8 and its associations with additional chromosome aberrations was confirmed in 7 adult and 3 pediatric patients with myelodysplastic syndromes treated with hematopoietic stem cell transplantation (HSCT). The group of comparison included 10 MDS patients with sole monosomy 7 or 5 chromosome and those within complex karyotypes (CK). Cytogenetic investigations were carried out according to standard GTG and multi-colored fluorescence in situ hybridization (mFISH) techniques. Our data revealed significant difference in overall survival (OS) between the tested and control groups (p=0.045) thus being additional argument reinforcing the concept of favorable prognosis of trisomy 8 in HSCT-treated MDS patients. Eight of ten patients (5 with sole trisomy 8 and three with more complex karyotypes) are alive. Of the deceased patients, one had CK trisomy 8 was associated with poor-prognostic monosomy 7. In accordance with experimental findings Sloand et al., 2007, this favorable effect of trisomy 8 in MDS patients might be linked with inhibition of programmed cell death with anti-apoptotic proteins, including myc, which are activated in these cases and needs additional in-depth studies.